Becoming Hispanic: The negotiation of ethnoracial identity in US census interviews. Issue 4 (December 2018) - Leeman, Jennifer
Abstract Researchers across disciplines have analyzed the ethnoracial classification of Latinxs in the US census, as well as the ideological, political, and material underpinnings and effects of such classification. In this article, I advance our understanding of the census' reproduction of racial identities and racial discourse in two ways. First, I demonstrate that sociolinguistic theory and methods can shed new light on census classification in three distinct areas: (1) the categories and classifications themselves, (2) the negotiation of ethnoracial classification during census interviews, and (3) the language in which censuses are conducted. Second, I demonstrate that census-taking does not consist simply of recording preexisting ethnoracial identities, or of disseminating official discourses from interviewers to respondents. Instead, census interviews involve the intersubjective construction and production of ethnoracial identities, as interviewers and respondents negotiate the meaning of the categories provided and their places within them.